EXCLUSION OF CONTRACTORS IN CONSTRUCTION CONTRACTS: AN UNREVEALED RISK IN THE CONSTRUCTION INDUSTRY - Geraldine J. KIKWASI (Journal of Construction Project Management and Innovation)
Contracting firms have been facing temporary and permanent exclusions from participating in tenders as result of not complying with Acts, rules and regulations of their respective countries. Exclusion intends to safeguard Governments and their citizens from unscrupulous contractors. This study seeks to determine risks associated contractors’ exclusion from participating in tenders. Using a descriptive research type, data were collected from a population of construction stakeholders. A selfadministered questionnaire, interviews, document reviews and literature review were used to collect data from randomly and purposely selected respondents. Quantitative data were analyzed by Statistical Package for Social Sciences (SPSS) through descriptive statistics mainly frequencies and descriptive, and Relative Frequency Index (RFI). Findings reveal varying trends of exclusion from one year to another. The top nine high risks associated with contractors ‘exclusion are delay of project completion time; increase in project costs; unpleasant reaction from donors or financiers; deferral of organizations strategic plans, mission and visions; development leaping; contractor’s loss of potential staff; contractor’s bankruptcy; contractor’s financial crises; and diversion and misallocation of resources. This implies that despite the valid reasons leading to contractors’ exclusion, there are hidden risks. The paper concludes that exclusion exists with disparities across years, the practice that poses several risks to contractors, clients, consultants and the nation at large. The paper recommends that responsible organs should assess risks associated with exclusion before its implementation.